Japan : 2007 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that Japan's external position remains strong. Boosted by investment income, the current account surplus widened in 2006 to nearly 4 percent of Japan's GDP, despite a shrinking trade balance. Financial outflows also picked up, reflecting mainly the secular decline in investor home bias and to a lesser extent, yen-financed carry trades. The near-term economic outlook is favorable. GDP growth is projected at 2.6 percent in 2007 and 2.0 percent in 2008. With activity close to full capacity, CPI inflation is expected to pick up, but very slowly.